2018
DOI: 10.3390/ijms19123758
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hybridization on Somatic Mutations and Genomic Rearrangements in Plants

Abstract: Hybridization has been routinely practiced in agriculture to enhance the crop yield. Principally, it can cause hybrid vigor where hybrid plants display increased size, biomass, fertility, and resistance to diseases, when compared to their parents. During hybridization, hybrid offspring receive a genomic shock due to mixing of distant parental genomes, which triggers a myriad of genomic rearrangements, e.g., transpositions, genome size changes, chromosomal rearrangements, and other effects on the chromatin. Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 89 publications
1
11
0
1
Order By: Relevance
“…However, in the origin of V. palustris, in addition to V. epipsila, a second unknown species having a GS that is not exactly the same as that of V. epipsila could have been involved. Although hybridization has been shown to have the potential to alter the GS (homoploid hybrid speciation, allopolyploidy), hybridization itself did not increase the GS, as demonstrated in studies on Helianthus hybrids [104,105]. The GS of the V. epipsila × V. palustris hybrids studied in the present research confirms this statement, because their 2C values were the sum of the haploid parental genomes.…”
Section: Lack Of Intraspecific Variation In Genome Sizesupporting
confidence: 80%
“…However, in the origin of V. palustris, in addition to V. epipsila, a second unknown species having a GS that is not exactly the same as that of V. epipsila could have been involved. Although hybridization has been shown to have the potential to alter the GS (homoploid hybrid speciation, allopolyploidy), hybridization itself did not increase the GS, as demonstrated in studies on Helianthus hybrids [104,105]. The GS of the V. epipsila × V. palustris hybrids studied in the present research confirms this statement, because their 2C values were the sum of the haploid parental genomes.…”
Section: Lack Of Intraspecific Variation In Genome Sizesupporting
confidence: 80%
“…Chromosomal rearrangements were known to be triggered due to ‘genomic shock’ during hybridization [ 25 ]. The spontaneous mutations, novel chromosomal changes, and retrotransposon activations had been reported in several plant species during hybridization [ 26 , 27 ]. As the weedy rice accession is genetically distant to japonica cultivars [ 28 ], this mutation most likely spontaneously originated from this distant cross.…”
Section: Discussionmentioning
confidence: 99%
“…One study noted that “…hybrid offspring receive a genomic shock due to mixing of distant parental genomes, which triggers a myriad of genomic rearrangements, for example, transpositions, genome size changes, chromosomal rearrangements, and other effects on the chromatin (i.e., DNA structures). Recently, it has been reported that, besides genomic rearrangements, hybridization can also alter the somatic mutation rates in plants.” (Bashir, Mishra, Hasan, Mohanta, & Bae, 2018). This does not mean that these more intrusive methods should be avoided—in some cases, traditional breeding, mutagenesis, or hybridization may be quicker, easier, and more effective tools for genetic modification in plants, despite resulting genomic changes.…”
Section: Figurementioning
confidence: 99%
“…Recently, it has been reported that, besides genomic rearrangements, hybridization can also alter the somatic mutation rates in plants." (Bashir, Mishra, Hasan, Mohanta, & Bae, 2018). This does not mean that these more intrusive methods should be avoided-in some cases, traditional breeding, mutagenesis, or hybridization may be quicker, easier, and more effective tools for genetic modification in plants, despite resulting genomic changes.…”
mentioning
confidence: 99%